Futsal athletes food profile in sub-13, sub-15 and sub-17 categories - de Macêdo, Marcos Roberto (2017)
Objective: To identify the profile of food consumption of macronutrients in indoor soccer players in Sub-13 categories, Sub-15 and Sub-17. Materials and Methods: This is a descriptive study, conducted with 46 male athletes with a minimum height of 1,36m and maximum 178 cm, minimum weight 32,00kg and maximum 62,55kg, in sub categories 13 (n = 12), 15 (n = 21), 17 (n = 14). The study was based on documentary analysis of the project. usual food recall was used to investigate the pattern of consumption of the athletes, this usual food recall recorded the types of food and the quantity, in household measures, consumed the last 24 hours by the athlete. Data were analyzed by Avanutri® program and compared to the recommendations. Data collection was carried out before the team training, the usual food recall was applied individually. Statistical analysis Descriptive. Results and Discussion: The protein intake the Sub-13 was 15.85%, the Sub-15 was 15.48% and the Sub-17 was 15,41%. The average consumption of carbohydrates the Sub-13 was 57.54%, the Sub-15 was 62.33% and the Sub-17 was 59.37. The average consumption of Lipids Sub-13 was 25.92%, the Sub-15 was 20.04% and the Sub-17 was 23.04%. Conclusion: Thus we can conclude that the present food consumption in athletes of the Sub-13 categories, Sub-15 and Sub-17 are at odds with the nutritional recommendations. In this sense it is likely to have these athletes losses in performance.